Oxidative and haemato-biochemical alterations in theileriosis affected cattle from semi arid endemic areas of India - PANDEY, VIJAY; NIGAM, RAJESH; BACHAN, RAM; SUDAN, VIKRANT; JAISWAL, AMIT KUMAR; SHANKAR, DAYA; KUMAR, RAHUL; MANDIL, RAJESH; YADAV, BRIJESH (The Indian Journal of Animal Sciences, 2017)
Blood samples were collected from 30 confirmed theileriosis affected adult cows belonging to a single herd. The infection of theileriosis in suspected and healthy cows was confirmed based on clinical signs, blood smear examination and PCR based assay. The collected blood samples were evaluated for levels of Hb, PCV, MCV, MCH, MCHC, DLC, LPO, GSSG, SOD, CAT, GST and AST. The results revealed substantial decrease in levels of Hb, PCV, MCH, MCHC, lymphocytes, SOD, CAT, GST and GSH and increase in LPO, AST, and neutrophils in infected animals compared to healthy animals. The association observed between enhanced erythrocytic oxidation and reduction of hematological indices suggests that antioxidant mechanisms of erythrocytes that protect them against oxidative damage may be disturbed during theileriosis which lead to erythrocytic destruction and progression of the anaemia in T. annulata infection in cows.